The influence of rounded corners on the performance of single-coped beam with slender web. (December 2021) - Lam, Chi Chiu; Cai, Jingming; Gu, Jiaming; Zhang, Yufei
Abstract: The rounded corners have significant influences on the buckling processes and carrying capacity of thin-walled steel structures. This paper was intended to investigate the influences of rounded corners on the performance of single-coped beam with slender web. The mechanical behaviours of two typical single-coped beams with different coped depths were experimentally investigated first. The finite element (FE) model was proposed and the accuracy was verified by comparing it with the experimental results. Based on the proposed FE model, the influences of different radius for rounded corners ( R c ) were investigated. It was concluded that the application of rounded corners has great impacts on the failure modes and buckling processes of single-coped beams. It was also found that the energy-dissipating capacity as well as load carrying capacity increased significantly with the application of round corners, especially for single-coped beam with deep coped depth. The round corner index, which considered the influences of both rounded corner and coped depth, was proposed via fitting with the simulational results. A typical design example considering the round corner index was also provided and a more accurate result was achieved.